A Novel Single Propagation Path Multimode PA - Santos, Fávero Guilherme; Mariano, André Augusto; Leite, Bernardo (Symposium on Integrated Circuits and Systems Design (SBCCI); 2020: Anais do XXXIII Symposium on Integrated Circuits and Systems Design, 2020)
In this paper a novel configuration of a power amplifier (PA) with a single propagation path is presented. It produces multimode operation by acting on the levels of AC voltages swings of a stacked architecture. The configuration is supported by two main concepts: consecutive voltage amplifications and selecting the operation modes of transistors (as an amplifier or as a switch) via different biasing levels. By combining these concepts, it is possible to select the output power delivered to the load, due to the number of transistors that will operate adding power to the output signal. The concept is tested at 2.4 GHz and on a 130 nm RF CMOS process and obtained post-layout simulation results are reported. The proposed proof of concept has three efficiency profiles, namely: low-power (LP), medium-power (MP) and high-power (HP). At LP mode, it performs a 1 dB output compression point (OCP 1dB ) of 16.8 dBm with a power added efficiency (PAE) of 28.1 %. At MP mode, it performs an OCP 1dB of 18.1 dBm with a PAE of 28.9 %. Lastly, HP mode performs an OCP 1dB of 19.9 dBm with a PAE of 25.7 %.